The effect of using antihypertensive drugs in hypertensive patients with kidney failure in hospital outpatients, Jember regency - Savania Alifianty Hafzah, Savania; Mayasari, Shinta; Khrisna Agung Cendekiawan (Sean Institute, 2024)
Hypertension was a condition where systolic blood pressure was more than equal to 140 mmHg and diastolic was more than equal to 90 mmHg after two separate measurements and was one of the main risk factors for kidney failure because it can cause damage to blood vessels in the kidneys so that reduces the ability of the kidneys to filter blood properly. Hypertension was a disease with a high incidence rate worldwide and was a cause of death, around 1.13 billion people in the world have hypertension and its complications, therefore the aim of this study was to determine the effect of using antihypertensive drugs in hypertensive patients with kidney failure in hospital outpatients, jember regency. In a study using a cross-sectional design, the population in this study were all hypertensive patients with kidney failure who were outpatients in hospital outpatients, jember regency in the period December 2022-March 2023. The number of samples used probability sampling with the proportionate stratified random sampling technique as many as 100 patients in hospital outpatients, jember regency. The results of this study indicate that there was an effect of using antihypertensive drugs in hypertensive patients with kidney failure. Based on the output of